Business research productivity and barriers. (2019) - Khalil, Omar E.M.; Khalil, Nadia
Knowing why some faculty members are more scholarly productive than others and what factors influence research productivity in an institution is essential to guiding research productivity improvement efforts. This study explored the research productivity and perceived research barriers to conducting research by the business faculty members at the Kuwait University (KU) as well as the influence of their individual characteristics on the reported productivity and barriers. The reported business research productivity tends to be low. Barriers related to research efficacy, physical and information resources, fiscal resources, and time reportedly challenge research productivity. However, the individual characteristics of gender, age, nationality, academic rank, experience at HE, time spent on research, and time spent on teaching variably influence the reported research productivity and perceived research barriers. These findings as well as their implications and limitations are further discussed in the paper.